The little lost hen... and other stories - Blyton, Enid; Byrnes, Lynne (London: Bounty books, 2015)
This magical story collection will have children laughing out loud at the silly characters and cute storylines. The book includes the stories of 'Billy-Bob's Coconut', 'Sammy the Scribbler', and 'The Wrong Bus'. Find out what's going on in toyland and beyond in this lovely set of tales from Enid Blyton
Keywords: English , Fiction